Pengembangan LKPD Materi Trigonometri Berbasis Generative Learning di Kelas X - Nurdiyanto, Tito; Hartono, Yusuf; Hartono, Indaryanti (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
This study was intended to produce a learner worksheet in trigonometry material based on generative learning with valid and practical, and to determine the potential effects on students conceptual understanding in trigonometry material. It is Research and Development with Borg and Gall model. The subjects of this research were students of class XI MIPA 4 SMAN 11 Palembang as many as 34 students. Data collection techniques used are interviews, observations, and test. The result of data analysis could be concluded that this research procuded worksheet in trigonometry material based on generative learning valid and practical trigonometry material, and LKPD that had been developed had a potential effect on students conceptual understanding in trigonometri material. Therefore worksheet that had been developed can be used by the students.